2007
DOI: 10.7863/jum.2007.26.9.1137
|View full text |Cite
|
Sign up to set email alerts
|

A New Parameter for Staging Bladder Carcinoma

Abstract: Objective. The purpose of this study was to investigate the value of tumor-bladder wall contact length (CL), tumor height (H), and height-to-length ratio (H/CL) for preoperative staging of bladder carcinoma. Methods. Fifty-seven patients with bladder tumors underwent suprapubic ultrasonography preoperatively, and the CL of the tumor with the bladder wall and H in the bladder lumen were measured. The CL, H, and H/CL values were correlated with the wall invasion determined by histopathologic analysis of the cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The author posits that the aspect ratio may be a superior indicator for evaluating morphological characteristics of tumors compared to basal and height measurements, even if it was not included as a reference standard in the nomogram. For example, the aspect ratio is frequently utilized in predicting BUC staging, and one study have shown that when the aspect ratio is <0.605, it suggests a heightened likelihood of myofilament infiltration [ 21 ]. Tumor-wall interface, when used along, is the most effective independent risk factor for identifying BUC and IPB.…”
Section: Discussionmentioning
confidence: 99%
“…The author posits that the aspect ratio may be a superior indicator for evaluating morphological characteristics of tumors compared to basal and height measurements, even if it was not included as a reference standard in the nomogram. For example, the aspect ratio is frequently utilized in predicting BUC staging, and one study have shown that when the aspect ratio is <0.605, it suggests a heightened likelihood of myofilament infiltration [ 21 ]. Tumor-wall interface, when used along, is the most effective independent risk factor for identifying BUC and IPB.…”
Section: Discussionmentioning
confidence: 99%
“…Ozden et al [ 3 ] performed a comparative analysis of the tumor height, the contact length between the tumor and bladder wall, and the ratio of invasive bladder cancer to non-invasive bladder cancer, and concluded that the tumor height, the contact length between the tumor and bladder wall, and the ratio of the two are closely related to the depth of bladder cancer invasion. The contact length was more than 41.5 mm, and the ratio of the two was less than 0.605, which is the critical value for distinguishing superficial and invasive bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Papillary tumors are benign and papillary urothelial tumors with low malignant potential are borderline tumors, both of which have a relatively good prognosis [ 7 ]. Although both low- and high-grade urothelial carcinomas are malignant epithelial tumors, the risk of progression of high-grade BUC is five times higher than that of low-grade BUC, which often requires more active treatment such as cc and postoperative perfusion chemotherapy [ 3 , 8 ].Therefore, accurate preoperative diagnosis and BUC grading is imperative in the selection of clinical operation methods and the prognostic evaluation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The author posits that the aspect ratio may be a superior indicator for evaluating morphological characteristics of tumors compared to basal and height measurements, even if it was not included as a reference standard in the nomogram. For example, the aspect ratio is frequently utilized in predicting BUC staging, and one study have shown that when the aspect ratio is < 0.605, it suggests a heightened likelihood of myo lament in ltration [21]. Tumor-wall interface, when used along, is the most effective independent risk factor for identifying BUC and IPB.…”
Section: Discussionmentioning
confidence: 99%